2013
DOI: 10.1111/nph.12620
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and robustness of the flavonoid transcriptional regulatory network revealed by comprehensive analyses of MYB–bHLHWDR complexes and their targets in Arabidopsis seed

Abstract: SummaryIn Arabidopsis thaliana, proanthocyanidins (PAs) accumulate in the innermost cell layer of the seed coat (i.e. endothelium, chalaza and micropyle). The expression of the biosynthetic genes involved relies on the transcriptional activity of R2R3-MYB and basic helix-loop-helix (bHLH) proteins which form ternary complexes ('MBW') with TRANSPARENT TESTA GLAB-RA1 (TTG1) (WD repeat protein). The identification of the direct targets and the determination of the nature and spatio-temporal activity of these MBW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
363
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(378 citation statements)
references
References 62 publications
14
363
1
Order By: Relevance
“…As shown in Supplemental Figure S4, both MtPAR and MtMYB14 rescued the Arabidopsis tt2 phenotype (leading to dark seed coats), supporting the conclusion that MtPAR and MtMYB14 are functional orthologs of Arabidopsis TT2. Although Xu et al (2014) observed that AtMYB5 could partially rescue the tt2 phenotype, we did not observe such rescue with MtMYB5.…”
Section: Identification Of Mtmyb5 and Mtmyb14contrasting
confidence: 45%
“…As shown in Supplemental Figure S4, both MtPAR and MtMYB14 rescued the Arabidopsis tt2 phenotype (leading to dark seed coats), supporting the conclusion that MtPAR and MtMYB14 are functional orthologs of Arabidopsis TT2. Although Xu et al (2014) observed that AtMYB5 could partially rescue the tt2 phenotype, we did not observe such rescue with MtMYB5.…”
Section: Identification Of Mtmyb5 and Mtmyb14contrasting
confidence: 45%
“…The MBW complex interacts directly with promoter DNA via multiple cis-elements. Known target sequences include the Myb-response element and AC elements for R2R3-MYB proteins and the E-box or bHLH-binding motif, which is bound by the bHLH proteins (Feller et al, 2011;Lai et al, 2013;Xu et al, 2014). In contrast, WDR proteins have not been shown to bind DNA but are thought to function by interacting with MYB and bHLH proteins (Baudry et al, 2004).…”
mentioning
confidence: 99%
“…Depending on the plant lineage, these transcriptional regulatory proteins may affect all biosynthetic genes in a single module (as in maize [Zea mays]) or separately, regulating the so-called late structural genes, like in petunia (Petunia hybrida), snapdragon (Antirrhinum majus), and Arabidopsis (Arabidopsis thaliana; Mol et al, 1998). In these species, the expression of the early biosynthetic genes is controlled by other regulators (sometimes redundantly with the MBW complex; Tornielli et al, 2009;Xu et al, 2014). In some cases (e.g.…”
mentioning
confidence: 99%
“…The phenylpropanoid pathway is finely tuned and tightly controlled by transcription factors (Albert et al, 2011;Xu et al, 2014). In this control, several protein families participate and mutually interact, giving rise to regulatory specificity (Grotewold et al, 2000).…”
mentioning
confidence: 99%